CONCEPTUAL ANALYSIS ON TIME (KĀLA) AND TRUE SELF (ĀTMAN) IN BRAHMA VIDYĀ, MANUSMṚTI, AND BHAGAVAD GĪTĀ - I Made Wirajana; Erika Gunawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study examines the concept of time (kāla) and the transcendent self (ātman) within the framework of Brahma Vidyā through an analysis of classical Hindu texts, particularly the Manava Dharmasastra and Bhagavad Gītā, employing a qualitative approach based on library research and conceptual hermeneutics. The findings reveal that kāla is understood not merely as a chronological measure, but as a cosmic-theological principle that governs the order of the universe, the rhythms of life, and the fulfillment of dharma. In the Manusmṛti, time functions as a normative cosmic structure supporting ethical and social harmony, whereas in the Bhagavad Gītā, it is presented as a direct manifestation of divine power regulating the cycles of creation, preservation, and dissolution. In contrast, ātman is understood as an eternal, transcendent reality that surpasses temporality, thus the relationship between kāla and ātman exhibits a dialectic between phenomenal reality and absolute consciousness. This conceptual synthesis affirms that time serves as a pedagogical-spiritual medium guiding humanity toward true self-awareness and realization of unity with Brahman. Consequently, the understanding of time from the perspective of Brahma Vidyā holds philosophical, theological, and practical spiritual significance as a foundation for shaping a life aligned with dharma and oriented toward liberation.